Investigation of pathogenic determinants in vibrio harveyi and screening of antogonistic bacteria for control of its infection - Pimonsri Rattanama (Prince of Songkla University, 2012)
Thesis (Ph.D., Biomedical Sciences)--Prince of Songkla University, 2010